(untitled) (SCIÉNDO INGENIUM, 2022)
The objective of this study is to design a system for the treatment and reuse of water from the washing machines of the hotel industry in the Trujillo district. The study was carried out with a sample of 100 hotels located in the Trujillo district. For the elaboration of the design of the treatment system, the diagnosis on the monthly water consumption in m3 was elaborated. Some quality parameters were analyzed and the design of the system was formulated. The result was a system with two tanks, one for treatment and the other for reuse. With the implementation of the water reuse system for the washing machines in the hotel industry, a saving of 25.5% of total water consumption is obtained and 72% of the managers of the hotels state that they are interested in a reuse system of water.